Enteric Organisms Detected in Feces of Dogs With Bloody Diarrhea: 45 Cases - Ramos, Carolina Pantuzza; Diniz, Amanda Nádia; Ribeiro, Marcio Garcia [UNESP]; de Paula, Carolina Lechinski [UNESP]; Costa, Érica Azevedo; Sonne, Luciana; Pereira, Silvia Trindade; Lopes, Carlos Eduardo Bastos; Rennó, Mário Cesar; Silva, Rodrigo Otávio Silveira (Elsevier, 2021)
Bloody diarrhea is a common condition in dogs, but studies evaluating the enteropathogens involved specifically in adult dogs are scarce. In the present study, stool samples from 45 adult dogs with bloody diarrhea were evaluated for the four enteric organisms mainly reported in these cases: canine parvovirus type 2 (CPV-2), Clostridioides difficile, Clostridium perfringens, and Salmonella spp. In addition, the samples were also tested for coronavirus, rotavirus, Giardia spp., and Escherichia coli pathotypes to provide a better understanding of possible co-occurrence. Vaccination status, diet, and clinical outcome were also obtained when available. CPV-2b was identified in 17 dogs (37.8%), being the most frequent cause of bloody diarrhea, including completely vaccinated adult dogs. Toxigenic C. difficile and C. perfringens netF+ were detected in 6 (13.3%) and 5 (11.1%) dogs, in some cases in a co-occurrence with other enteric organisms. Three fatal cases of salmonellosis were identified in dogs fed a raw meat-based diet, raising the risks associated with this increasing practice.
Keywords: clostridioides difficile; clostridium perfringens; parvovirus; raw meat-based diets; salmonella